Repositioning Culture in International Relations: Confucianism as Geopolitical Instrument - Amalia, Ariffah Isna (Department of International Relations, Brawijaya University, 2021)
Confucianism is a culture taken from the name of a thinker, namely Confucius, and is considered the basis of Confucian teachings. The primary view of Confucianism is to invite people to live an orderly, peaceful, and happy life replacing the rulers as one of the key factors in achieving country ideals. This study aims to identify and evaluate the chronology of Confucianism and its implications for China's geopolitical sustainability. The method used is qualitative with constructivist ideas to create a comprehensive thought allocation on the impact of Confucianism from the perspective of cultural superiority. The results obtained are that, over time, Confucianism has developed into a tool for the Chinese state to carry out geopolitical instruments to achieve geostrategy for expanding territorial boundaries. On the one hand, Confucianism can become a superior culture that places the people's fighting spirit. On the other hand, this flow can become a trigger for war when each region to be recruited for China's expansion has a culture and beliefs different from their own. Keywords: Confucianism, China, Geopolitics, Geostrategy